A study on existing practices in selected law libraries in answering legal reference questions - Bernardo, Cyril John M. (School of Library and Information Studies, University of the Philippines Diliman, 2018)
The practice of law librarianship in the Philippines is a little-explored profession as evinced by the lack of literature to discuss it. Of particular interest is how law libraries answer legal reference questions. This is because of the peculiarity of the type of information dealt with, as well as legal (e.g. unauthorized practice of law) and other concerns (e.g. providing accurate, current, and comprehensive answers). Interviews with law librarians and library staff from selected institutions have been conducted, with the transcript and notes subjected to thematic analysis. Codes were picked from the materials yielded by the interviews, and these were then organized into themes. These themes of respondent institution were then compared and analyzed. The study showed that law librarians primarily use the reference interview in responding to the queries, and they draw from a varied array of resources supplemented by various connections. Law librarians could become more effective in their practice if they receive adequate support in terms of resources, staff, and guidelines.